Brewing resilience for Ethiopia’s smallholder coffee farmers: A closer look at Ethiopia’s coffee sector to help address climate information gaps - Ventocilla, Maria Claudia; Grossi, Amanda; Hernández Aguilera, J. Nicolas; Dinku, Tufa; Recha, John W.M.; Ambaw, Gebermedihin (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
A powerhouse in coffee production—Africa’s largest—and a place where more than 15 million people rely on the sector for their livelihoods (Petit 2007), Ethiopia is the world’s fifth-largest exporter of Arabica coffee (Moat et al. 2017), a product that represents 34% of the nation’s total export earnings (USDA 2019). Considering 70% of the total coffee traded in the world is Arabica, it is no surprise that 100% of Ethiopian coffee production is of this species (Kew & ECFF 2017). What is more, the country is considered the center of origin and genetic diversity of Arabica coffee (ECFF 2015). Although this species has a relatively high market value due to its exceptional quality, its production is, nonetheless, extremely sensitive to climate variability (Davis et al. 2012). It is estimated that by the end of the century climate could render 39-59% of Ethiopia’s coffee-growing areas unsuitable for cultivation (Moat et al. 2017).